2016
DOI: 10.1111/bcp.13099
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the variation in the concentration of acetylcysteine in infusions for the treatment of paracetamol overdose

Abstract: BACKGROUNDIntravenous acetylcysteine is the treatment of choice for paracetamol poisoning. A previous UK study in 2001 found that 39% of measured acetylcysteine infusion concentrations differed by >20% from anticipated concentrations. In 2012, the UK Commission on Human Medicines made recommendations for the management of paracetamol overdose, including provision of weight-based acetylcysteine dosing tables. The aim of this study was to assess variation in acetylcysteine concentrations in administered infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
0
20
2
Order By: Relevance
“…Our group and others have previously hypothesized that inadequate mixing of infusions may result in heterogeneous concentrations of acetylcysteine within the infusion fluid . Results from this study, however, indicate that mixing does not play a substantial role in the variation of infusion concentrations.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Our group and others have previously hypothesized that inadequate mixing of infusions may result in heterogeneous concentrations of acetylcysteine within the infusion fluid . Results from this study, however, indicate that mixing does not play a substantial role in the variation of infusion concentrations.…”
Section: Discussioncontrasting
confidence: 77%
“…Our study did not reproduce findings from previous studies that had shown a large variation in acetylcysteine infusion concentrations . This may be partially due to the fact that our experiments were conducted by a single researcher who was aware that the concentration of the samples would be assessed and the infusions were prepared in a laboratory environment rather than a comparatively chaotic ward or emergency department environment.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Bailey et al . found that half of the bags deviated by >10% between measured and expected concentrations . One in five deviated by >20%.…”
Section: Nomenclature Of Targets and Ligandsmentioning
confidence: 99%